Autoantibodies, complement and type I interferon as biomarkers for personalized medicine in SLE. (July 2016) - Biesen, R; Rose, T; Hoyer, B F; Alexander, T; Hiepe, F
Systemic lupus erythematosus (SLE) can be a mysterious disease, presenting with extremely divergent clinical phenotypes. Already, biomarkers are very helpful tools for diagnosis, assessment and monitoring of disease activity, differential diagnosis of clinical manifestations, prediction of the disease course and stratified therapy, and they hold the key to personalized medicine in SLE. We summarize the clinical information that can only be supplied by autoantibodies, complement components and interferon biomarkers in this diverse disease.